A relational view of self-protection amongst China's food safety crises. Issue 1 (2nd January 2019) - Lin, Haiying; Fang, Ping; Zhou, Li; Xu, Licheng
ABSTRACT: This article adopts a relational view to unpack farmers' self-protection mechanisms and alternative safe food access when food safety crises escalate in China. It integrates literature from psychological and agricultural economy studies to investigate the obligational and emotional relationships between farmers and outside parties. Building on inductive analysis based on 60 farmers in Shouguang County at Shandong Province, China, we identified four types of interpersonal relationships developed by farmers. We further developed an emotion-obligation matrix to examine the relational boundary between "insiders" and "outsiders". We noted that when balancing relational versus economic interests, farmers tend to provide insiders with "family food" and outsiders with "stranger food".